The Relationship between Self-Efficacy, School Climate, and Student Engagement in Elementary Education - Muhammad Noor; Pranciska Gamilina (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although self-efficacy, school climate, and student engagement are widely recognized as important determinants of academic participation, empirical understanding of their interrelated dynamics in elementary education remains limited. This study aims to examine the individual and collective relationships among self-efficacy, school climate, and student engagement among upper-grade elementary students. A quantitative correlational approach was employed, involving 43 students selected through total sampling. Data were collected using Likert-scale instruments and analyzed using Pearson correlation, multiple regression, and first-order partial correlation with IBM SPSS Statistics 25. The findings reveal that self-efficacy has a statistically significant positive relationship with student engagement (r = 0.606, p < .05), as does school climate (r = 0.570, p < .05). Together, self-efficacy and school climate explain 43.8% of the variance in student engagement (R² = 0.438, p < .05). Partial correlation analysis further confirms that self-efficacy (r = 0.409, p < .05) and school climate (r = 0.332, p < .05) each remain significantly associated with student engagement after mutual statistical control. These findings indicate that student engagement in elementary education is shaped by both intrapersonal factors and contextual learning environments. This study contributes to educational psychology and elementary education literature by integrating personal and environmental perspectives on student engagement. Practically, the findings imply that schools should strengthen students’ self-belief while fostering supportive, inclusive, and motivating school climates to enhance learning engagement. Keywords: Self-Efficacy; School Climate; Student Engagement; Elementary Education; Learning Environment